Another Missed Opportunity? Underfunding Australian Higher Education - Welch, Anthony (International Higher Education, 2017)
In the context of a long period of underfunded higher education in Australia, the latest federal budget will do nothing to address the problem. While the worst elements of former proposals were averted, the shifting of more of the burden of repaying student loans on to students, as well as failing to fund the full costs of research, and, in addition, imposing further “‘efficiency dividends”’ on higher education institutions, will only add to institutional pressures to diversify income, increasing international student fees.